Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species - Crispolon, Elorde Jr. S.; Yap, Sheryl A.; Soulier-Perkins, Adeline (Zootaxa, 2019)
The genus Poeciloterpa Stål endemic to the Philippines with 9 known species is reviewed. Four new species are described and illustrated: P. altissima Crispolon et Soulier-Perkins sp. nov., P. conica Crispolon et Soulier-Perkins sp. nov., P. gapudi Crispolon et Yap sp. nov. and P. mangkas Crispolon et Yap sp. nov. Illustrations and descriptions for the male genitalia are given for the first time for all the species except for P. nigrolimbata Stål known only by two female specimens. A key to species is provided. The type of habitats where the species are found is discussed and new host-plants listed.